2015
DOI: 10.1521/pedi_2014_28_152
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Gene Variation and Differential Susceptibility to Family Environment in Predicting Youth Borderline Symptoms

Abstract: Oxytocin appears to be centrally involved in socioemotional functioning, and is hypothesized to be relevant to the severe disruption in close relationships characteristic of borderline personality pathology. We examined whether a polymorphism of the oxytocin receptor gene (OXTR rs53576) interacts with quality of family functioning to predict borderline personality disorder (BPD) symptomatology in a sample of youth at age 20. A total of 385 youth from a longitudinal study of offspring of depressed or nondepress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 47 publications
3
52
3
1
Order By: Relevance
“…As regards (epi‐)genetics of the oxytocinergic system, there is some evidence in support of the view that variation of the OXTR gene follows a pattern consistent with differential susceptibility to environmental conditions (Amad et al ., ; Cicchetti et al ., ; Ellis, Shirtcliff, Boyce, Deardorff, & Essex, ; Hammen et al ., ) and that methylation of the OXTR through stressful early experiences may act as a proxy for the intergenerational transmission of insecure attachment patterns (van Ijzendoorn et al ., ). This perspective may have implications for the prevention of non‐genetic transmission of BPD over successive generations (Newman, Stevenson, Bergman, & Boyce, ; Stepp, Whalen, Pilkonis, Hipwell, & Levine, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards (epi‐)genetics of the oxytocinergic system, there is some evidence in support of the view that variation of the OXTR gene follows a pattern consistent with differential susceptibility to environmental conditions (Amad et al ., ; Cicchetti et al ., ; Ellis, Shirtcliff, Boyce, Deardorff, & Essex, ; Hammen et al ., ) and that methylation of the OXTR through stressful early experiences may act as a proxy for the intergenerational transmission of insecure attachment patterns (van Ijzendoorn et al ., ). This perspective may have implications for the prevention of non‐genetic transmission of BPD over successive generations (Newman, Stevenson, Bergman, & Boyce, ; Stepp, Whalen, Pilkonis, Hipwell, & Levine, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent study reported a diametrically opposite finding, whereby A‐allele carriers of the same SNP had high levels of BPD symptoms when raised by depressed mothers and low levels when grown up in families with non‐depressed mothers. GG homozygotes were unresponsive to early rearing conditions, suggesting that the SNP rs53576 of the OXTR gene could confer ‘differential susceptibility’ to environmental contingencies (Hammen, Bower, & Cole, ). The concept of differential susceptibility suggests that a particular allele can be associated with opposite outcomes concerning psychological traits, depending on the quality of early environmental experiences (Belsky et al ., ; Boyce & Ellis, ).…”
Section: Oxytocin System In Bpdmentioning
confidence: 99%
“…It must be acknowledged however that not all findings support the notion of OXTR rs53576 G allele carriers being more sensitive to the social environment (Hammen et al, 2015; McInnis et al, 2015; Thompson et al, 2014). For instance, OXTR rs53576 moderated the relationship between exposure to maternal depression in childhood and depressive symptoms at age 15 years (Thompson et al, 2014).…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 92%
“…Presence of at least one A allele conferred higher risk to depressive symptoms in individuals whose mothers reported at least one episode of MDD during the child’s lifetime. There is also evidence for a differential susceptibility to develop symptoms of Borderline personality disorder (BPD) at age 20 in response to family quality in adolescence (Hammen et al, 2015). Under conditions of low familial constraint, presence of at least one A allele was associated with lower BPD symptoms compared to G allele homozygous participants, whereas under high family discord A allele carriers were more likely to develop more severe BPD symptoms than G allele homozygotes.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
See 1 more Smart Citation